Prevention of doxorubicin cardiac toxicity in the mouse by N-acetylcysteine. - Doroshow, J H (1981)
This study was undertaken to investigate the effect of exogenous sulfhydryl compound administration on the toxicity of doxorubicin in mice. Pretreatment of CDF1 mice with a pharmacologic dose (2,000 mg/kg) of n-acetyl-l-cysteine 1 h before doxorubicin (20 mg/kg, i.p.) decreased lethality from 100% (n = 44) to 37.7% (n = 53), P less than 0.001. Variation in the timing and dose of n-acetylcysteine significantly diminished its protective activity. Pretreatment with n-acetylcysteine also significantly reduced long-term mortality in animals receiving multiple doses of doxorubicin; 10 wk after the third of three doxorubicin doses (5 mg/kg, i.p.) administered at 2-wk intervals, survival in the n-acetylcysteine pretreated group was 51.4% (n = 35) compared with 16.7% (n = 30) for animals receiving saline before doxorubicin, P less than 0.01. In this experiment, n-acetylcysteine pretreatment also diminished doxorubicin-related losses in total body weight and heart wet weight by 55.2% (P less than 0.05), and 60.9% (P less than 0.02), respectively, compared with animals pretreated with saline. N-acetylcysteine pretreatment also ablated electron microscopic evidence of doxorubicin cardiomyopathy without alleviating morphological features of its toxic effects on the liver or small intestinal mucosa. The cardioprotective action of n-acetylcysteine may be partially explained by the 429 +/- 60% increase in cardiac nonprotein sulfhydryl content (P less than 0.01) that was measured one hour after n-acetylcysteine administration; nonprotein sulfhydryl concentration in the liver at the same time was insignificantly different from control levels. Treatment with n-acetylcysteine also increased the nonprotein sulfhydryl content of P388 leukemia cells nearly threefold; however, it did not after the chemotherapeutic activity of doxorubicin against this murine tumor. Whereas n-acetylcysteine blocked doxorubicin cardiac toxicity, it did not affect the uptake or metabolism of doxorubicin in the heart or liver. These results suggest that the concentration of free sulfhydryl groups in the heart may play a role in the development of doxorubicin cardiac toxicity and that augmenting cardiac nonprotein sulfhydryl group content with n-acetylcysteine may provide a means to enhance the chemotherapeutic index of doxorubicin.